Menelusuri Lembaga Pendidikan Islam SDI Asy-Syuhada’ Pamekasan Sebagai Strategi Membentuk Siswa Berkeagamaan dan Cinta Masjid - Hamdani, Hamdani; Utami, Tika Hestiarini; Maimun, Maimun (Adabuna : Jurnal Pemikiran dan Pendidikan, 2024)
SDI Asy-Syuhada' is a basic educational institution under the auspices of the ta'mir of the Jami' Asy-Syuhada' Pamekasan mosque. As a strategic location near the mosque, SDI Asy-Syuhada' takes advantage of this situation in order to form students who are religious and love the mosque. The aim of this research is to find out the strategies of school principals and teachers in forming students who are religious and love mosques. The method used is descriptive qualitative. Researchers go directly into the field to look for the data needed according to the object being studied. The results of this research are that: 1) The religious strategy is carried out with a view of the Prophet and is followed by the description made by the teacher himself and by making a habit as a coach that what has been learned can be carried out in everyday life. 2) the strategy to love the mosque, the program created is midday prayers in congregation and cleaning the mosque environment. The results of the research can be a reference for educators or educational institutions who have the same desires and targets by implementing the same strategy in creating students who are religious and love mosques.